Ar-Based Gamon (Good Attitude Make Our Nation) Innovative Learning To Build Naturalist Intelligence - Amanatul Uluwiyah; Alif Mudiono; Eny Nur Aisyah (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
This study aims to identify the development of children's naturalist intelligence after participating in learning activities using Augmented Reality (AR)-based puzzles, and to explain how social values ​​such as cooperation, sharing, and mutual assistance emerge during group activities. This study used a qualitative descriptive approach and was conducted in a kindergarten. Data sources were obtained through observation, interviews, questionnaires, and group discussions with teachers and students. Data analysis was carried out through data reduction, data presentation, and the drawing of interpretive conclusions. The results show that the use of AR puzzles improves children's naturalist intelligence, as reflected in their ability to recognize natural objects, distinguish plant and animal types, and show interest in exploring information about the environment. In addition, social values emerged naturally during the activities, where children collaborated on puzzles, took turns, offered assistance, and discussed in groups. The implications of this study confirm that AR-based media not only enriches visual learning experiences but also effectively develops cognitive and social aspects of early childhood. Therefore, teachers can utilize AR as an alternative interactive and collaborative thematic learning media.